2021
DOI: 10.1017/s1049023x21000583
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Prehospital Heat Illness Cases During the Annual Heat Wave Period in Telangana, India

Abstract: Objectives: Global warming and more intense heat wave periods impact health. Heat illness during heat waves has not been studied in the prehospital setting of a low- and middle-income country (LMIC). Early intervention in the community and in the prehospital setting can improve outcomes. Hence, this paper aims to describe the characteristics of heat illness patients utilizing the ambulance service in Telangana state, India with the aim of optimizing public prevention and first aid strategies and prehospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Also, difficult terrain or geography and challenging weather can greatly affect prehospital transport, which is evident in the findings of studies conducted in Sierra Leone, 81 Iran, 85 and India. 84 Most of the studies suggested that the health outcome following prehospital care in LMICs is generally poor. Survival following cardiac emergencies like OHCA and severe trauma was low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, difficult terrain or geography and challenging weather can greatly affect prehospital transport, which is evident in the findings of studies conducted in Sierra Leone, 81 Iran, 85 and India. 84 Most of the studies suggested that the health outcome following prehospital care in LMICs is generally poor. Survival following cardiac emergencies like OHCA and severe trauma was low.…”
Section: Discussionmentioning
confidence: 99%
“…Also, difficult terrain or geography and challenging weather can greatly affect prehospital transport, which is evident in the findings of studies conducted in Sierra Leone, 81 Iran, 85 and India. 84 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation